PERAN PENDIDIKAN HUKUM DALAM MENINGKATKAN KESADARAN DAN KETAATAN HUKUM MASYARAKAT DI INDONESIA - Triwahyuningsih, Triwahyuningsih; Darojat, Abdurrahman (Jurnal Ilmiah Advokasi, 2025)
This study aims to analyze the role of legal education in enhancing legal awareness and compliance of society in Indonesia. The research employs a normative juridical method using a statute approach and a conceptual approach through the examination of scholars’ opinions. The data consist of primary, secondary, and tertiary legal materials, which were analyzed qualitatively through stages of data reduction, classification, interpretation, presentation, and conclusion drawing. The findings indicate that legal education, both through formal and non-formal channels, significantly contributes to fostering law-abiding citizens. First, legal education develops public knowledge of the principles of the rule of law in Indonesia. Second, it strengthens understanding of the content, objectives, benefits, and sanctions of legal rules. Third, it cultivates a positive attitude toward law based on accurate knowledge and comprehension. Fourth, it encourages consistent behavior in upholding legal norms and regulations. Therefore, legal education plays a strategic role in improving legal awareness and ensuring compliance with the law, ultimately contributing to the realization of a law-abiding society in Indonesia. Keywords: Legal Education; Legal Awareness; Legal Compliance; Indonesia